User Satisfaction of Intermodal Transportation Services at Nusantara Passenger Terminal, Tanjung Priok Port, Jakarta - Yusfita Chrisnawati; Winoto Hadi; Tegar Abdi Putro (Puslitbang Transportasi Antarmoda-Kementerian Perhubungan Republik Indonesia, 2020)
According to a strategic plan of Directorate General of Sea Transport, port accessibility has become one of the leading infrastructure development aims. The operator of the Nusantara Terminal in Tanjung Priok Port has provided an intermodal transport network through a variety of services. The presence of this intermodal transportation service must meet the quality of service that meets the satisfaction of its users. Quality of service reflects the perception of users of intermodal services that are highly dependent on intermodal service operational decisions made by the operator. The need to maintain market share and increase profits is the main impetus for improving the quality of intermodal transportation services. This study focuses on measuring user satisfaction and perceptions of intermodal transportation services provided by the Tanjung Priok Nusantara Terminal operator and analyzing what factors of intermodal transportation services need to be improved to meet user satisfaction. The measurement of service user satisfaction uses the Customer Satisfaction Index (CSI) calculation method. Meanwhile, the Importance Performance Analysis (IPA) method is used to analyze the factors that influence the satisfaction of service users. Data collection is done by direct observation in the field, the interview process, and the distribution of questionnaires to respondents to obtain data on perceptions and expectations of inter-modal transportation services. The calculation result of the Customer Satisfaction Index (CSI) shows that respondents are satisfied with the facilities and services presented by the terminal manager; this can be seen from the CSI value obtained, which is 71.79%. Calculation of Importance Performance Analysis (IPA) shows that the attributes that need to be improved include the second attribute